2016
DOI: 10.1007/s12273-016-0290-7
|View full text |Cite
|
Sign up to set email alerts
|

Person to person droplets transmission characteristics in unidirectional ventilated protective isolation room: The impact of initial droplet size

Abstract: Person to person droplets/particles or contaminant cross transmission is an important issue in ventilated environment, especially in the unidirectional ventilated protective isolation room (UVPIR) where the patient's immune system is extremely low and easily infected. We simulated the dispersion process of the droplets with initial diameter of 100 μm, 10 μm and gaseous contaminant in unidirectional ventilated protective isolation room and studied the droplets dispersion and cross transmission with different si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 33 publications
2
33
0
1
Order By: Relevance
“…In order to evaluate dynamic airborne transmission, a suitable evaluation method is required. In the context of steady‐state conditions, there are two widely used methods for evaluating the risk of cross‐infection, namely intake fraction (IF) and exposure index ( ε s ) …”
Section: Results and Analysismentioning
confidence: 99%
“…In order to evaluate dynamic airborne transmission, a suitable evaluation method is required. In the context of steady‐state conditions, there are two widely used methods for evaluating the risk of cross‐infection, namely intake fraction (IF) and exposure index ( ε s ) …”
Section: Results and Analysismentioning
confidence: 99%
“…This sequence was reversed using DV. A number of other studies examined different particle sizes, but they mostly had no conclusion on the influence of particle size on the risk of cross‐infection. Liu and Novoselac analyzed the spread behavior of 3 particle sizes (0.77, 2.5, and 7.0 μm) generated from a cough and reported that the larger particles have a lower concentration in the vicinity of the receiver occupant in front.…”
Section: Current Understanding Of Airborne Transmission Indoorsmentioning
confidence: 99%
“…However, they are low‐resolution in both space and time. As an alternative, CFD methods employing computational thermal manikins and well‐established mathematical models for the transport of tracer gas/particles can provide a high‐resolution whole‐field flow and concentration data . However, CFD simulations must be experimentally validated and they are very dependent on the knowledge of the practitioners.…”
Section: Introductionmentioning
confidence: 99%
“…24,36,52 Direct evidence of the human respiratory system as a sink for certain air contaminants supports the conclusion that air contaminants can be absorbed into human bodies. 24,36,52 Direct evidence of the human respiratory system as a sink for certain air contaminants supports the conclusion that air contaminants can be absorbed into human bodies.…”
Section: Discussionmentioning
confidence: 85%